Multicenter Prospective Study of Biomarkers for Diagnosis of Invasive Candidiasis in Children and Adolescents . (20th January 2022) - Fisher, Brian T; Boge, Craig L K; Xiao, Rui; Shuster, Sydney; Chin-Quee, Dawn; Allen, John; Shaheen, Shareef; Hayden, Randall; Suganda, Sri; Zaoutis, Theoklis E; Chang, Yeh Chung; Yin, Dwight E; et al.
Abstract: Background: Diagnosis of invasive candidiasis (IC) relies on insensitive cultures; the relative utility of fungal biomarkers in children is unclear. Methods: This multinational observational cohort study enrolled patients aged >120 days and <18 years with concern for IC from 1 January 2015 to 26 September 2019 at 25 centers. Blood collected at onset of symptoms was tested using T2Candida, Fungitell (1→3)-β-D-glucan, Platelia Candida Antigen (Ag) Plus, and Platelia Candida Antibody (Ab) Plus assays. Operating characteristics were determined for each biomarker, and assays meeting a defined threshold considered in combination. Sterile site cultures were the reference standard. Results: Five hundred participants were enrolled at 22 centers in 3 countries, and IC was diagnosed in 13 (2.6%). Thirteen additional blood specimens were collected and successfully spiked with Candida species, to achieve a 5.0% event rate. Valid T2Candida, Fungitell, Platelia Candida Ag Plus, and Platelia Candida Ab Plus assay results were available for 438, 467, 473, and 473 specimens, respectively. Operating characteristics for T2Candida were most optimal for detecting IC due to any Candida species, with results as follows: sensitivity, 80.0% (95% confidence interval, 59.3%–93.2%), specificity 97.1% (95.0%–98.5%), positive predictive value, 62.5% (43.7%–78.9%), and negative predictive value, 98.8% (97.2%–99.6%). Only T2Candida and Platelia Candida Ag Plus assays met the threshold for combination testing. Positive result for either yielded the following results: sensitivity, 86.4% (95% confidence interval, 65.1%– 97.1%); specificity, 94.7% (92.0%–96.7%); positive predictive value, 47.5% (31.5%–63.9%); and negative predictive value, 99.2% (97.7%–99.8%). Conclusions: T2Candida alone or in combination with Platelia Candida Ag Plus may be beneficial for rapid detection of Candida species in children with concern for IC. Clinical Trials Registration: NCT02220790. Abstract : In this multinational observational cohort study of children and adolescents with concern for invasive candidiasis, operating characteristics of the T2Candida assay alone or combined with the Platelia Candida Ag Plus assay support the potential clinical utility of these diagnostic tools.